EVALUASI PENERAPAN ISAK 35 PADA INDONESIAN CORRUPTION WATCH TAHUN 2020–2023 - Asih Sugihartina Nurmuliahayati; Agesty Lidya Pangestika; Rini Rohaeni; Tia Pratiwinyngsih; Nofryanti Nofryanti (Bajang Institute, 2025)
This research explores the extent to which the financial statements of Indonesian Corruption Watch (ICW) align with ISAK 35, which governs the presentation of financial reports for nonprofit-oriented entities, during the years 2020 to 2023. Employing a descriptive qualitative approach through a case study and document analysis, this study evaluates ICW’s adherence to the standard. The results indicate a progressive improvement in ICW’s financial reporting, demonstrating increased conformity with ISAK 35. Since the initial year of implementation, ICW has regularly included all five essential components in its financial disclosures: the statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows, and accompanying notes. Furthermore, from 2022 onwards, ICW has explicitly classified net assets into restricted and unrestricted categories and provided comprehensive disclosures regarding restricted funds. Compared to previous studies on nonprofit organizations, ICW demonstrates a higher level of compliance with ISAK 35 standards, reflecting its strong commitment to transparency and accountability. This achievement positions ICW as a model for best practices in nonprofit financial reporting, especially for organizations engaged in public advocacy and anti-corruption efforts in Indonesia.